A Context Dependent Interpretation of Inconsistencies in 2D:4D Findings: The Moderating Role of Status Relevance - Millet, Kobe; Buehler, Florian (Frontiers in Behavioral Neuroscience, 2018)
Whereas direct relationships between 2D:4D and dominance related attitudes or behavior often turn out to be weak, some literature suggests that the relation between 2D:4D and dominance is context-specific. That is, especially in status-challenging situations 2D:4D may be related to dominant behavior and its correlates. Based on this perspective, we interpret inconsistencies in the literature on the relation between 2D:4D and risk taking, aggression and dominance related outcomes and investigate in our empirical study how attitudes in low 2D:4D men may change as a function of the status relevance of the context. We provide evidence for the idea that status relevance of the particular situation at hand influences the attitude towards performance-enhancing means for low 2D:4D men, but not for high 2D:4D men. We argue that 2D:4D may be related to any behavior that is functional to attain status in a specific context. Implications for (economic) decision making are discussed.